ImproveCog, a cognitive stimulation program for people with mild cognitive impairment and dementia: First stage of development - Meireles,Laura (2021)
Abstract Cognitive stimulation seems to be an important tool to slow the rate of cognitive decline due to dementia. This study describes the development of a cognitive stimulation program (ImproveCog) for people with Mild Cognitive Impairment, Alzheimer’s Disease, and behavioral variant Frontotemporal Dementia, within the Medical Research Council framework. Stage 1 established the theoretical and evidence basis of the program through a review of the existing cognitive stimulation programs as well as cognitive exercises and their efficacy (Pre-Clinical Phase) and includes qualitative testing through five focus group with eighteen health professionals and twelve individual interviews with people with cognitive impairment (Phase I - Modeling). An initial version of the program, which consisted of twelve 90-min weekly sessions and included a manual with cognitive stimulation exercises to be performed at home, was ready to be implemented in a pilot study to create a final version of ImproveCog.